Experimental and Simulation for the Effect of Partial Shading on Solar Panel Performance (Journal of Engineering, 2016)
Partial shading is one of the problems that affects the power production and the efficiency of photovoltaic module. A series of experimental work have been done of partial shading of   monocrystalline PV module; 50W, Isc: 3.1A, Voc: 22V with 36 cells in series is achieved. Non-linear power output responses of the module are observed by applying various cases of partial shading (vertical and horizontal shading of solar cells in the module). Shading a single cell (corner cell) has the greatest impact on output energy. Horizontal shading or vertical shading reduced the power from 41W to 18W at constant solar radiation 1000W/m2 and steady state condition. Vertical blocking a column of cells (9 cells) in a module reduces the power from 41W to 18W (53% power reduction); while, blocking one or two cell in the row reduces the power from 41 W to 18W (53% power reduction). Shading three or four cells in the same row reduces the power from 41W to 1W or 0.006W (94% power reduction). A complete Matlab / Simulink model are achieved to simulate the effect of partial shading on power output of module. It is found that shading a single cell reduces the power from 50 W to 25 W (50%) using Matlab/Simulink model. Comparisons have been made between the I-V and P-V characteristic curves from the simulation with the practical (experimental) curves. The results showed that the percentage of error between the Simulink results and the corresponding experimental measurement are 22% without shading effect and, 32% with partial shading.